Physical activity and health guidelines recommendations for various ages, fitness levels, and conditions from 57 authoritative sources - Rahl, Riva L. 1973- (Human Kinetics, 2010)
Lifting through the numerous guidelines on physical activity and health published by government agencies, professional organizations, and associations can be a daunting task. Information exists in all types of formats and locations--including government documents, press releases, and Web sites--so simply finding those guidelines can be an ordeal. Physical Activity and Health Guidelines puts the current information in one place--at your fingertips. Physical Activity and Health Guidelines compiles the latest recommendations from various leading sources and organizations into a single text. This one-of-kind resource provides quick reference to physical activity and health recommendations for healthy people and for those with chronic conditions across all age groups. All readers--physicians, physical therapists, fitness professionals, and general fitness enthusiasts--will be able to locate individualized recommendations regarding appropriate levels and types of physical activity. Specific activity recommendations for people with diabetes, asthma, osteoarthritis, and cerebral palsy are detailed in this text. Other guidelines for the prevention of common chronic diseases such as cancer, coronary artery disease, osteoporosis, and metabolic syndrome are also shared. This text also includes the following information: The components of exercise program design, which will assist readers in preparing to implement individual and group exercise programs; How physical activity recommendations can help people meet weight-management guidelines; Information on purchasing and using exercise equipment such as treadmills, heart rate monitors, weight training machines, and exercise videos; Guidelines for cardiac testing and other exercise testing to assist in the implementation and evaluation of physical activity programs as well as the assessment of the safety of these programs for people with chronic conditions. For ease of use, Physical Activity and Health Guidelines presents information in a consistent format for each entry, including the date issued or most recently updated, the issuing organization, appropriate population, and location of the guidelines (with Web sites when available). Recommendations are given for aerobic, resistance, and flexibility training; further specifications regarding the frequency, intensity, duration, and type of activity are included. An appendix lists additional resources divided by topic and includes Web addresses of key organizations, statements, and other physical activity and health-related tools. Physical Activity and Health Guidelines is the first text to gather the wealth of information regarding physical activity, exercise, and health needs and recommendations into a single source. Convenient and easy to use, this unique text will help readers understand the requirements for safe and effective physical activity for all people regardless of health conditions, and it offers the basic knowledge and tools for designing and implementing appropriate physical activity programs.